Optimization of treatment strategies based on preoperative imaging features and local recurrence areas for locally advanced lower rectal cancer after lateral pelvic lymph node dissection - Xu, Zhao; Bao, Mandula; Cai, Qiang; Wang, Qian; Xing, Wei; Liu, Qian (Frontiers in Oncology, 2024)
Total mesorectal excision (TME); Local recurrence (LR); Locally advanced lower rectal cancer (LALRC); Neoadjuvant chemoradiotherapy (nCRT); Lateral pelvic lymph node (LPN); Lateral pelvic lymph node dissection (LPND); Japanese clinical oncology group (JCOG); Japanese Society for Cancer of the Colon and Rectum (JSCCR); computed tomography (CT); magnetic resonance imaging (MRI); clinical circumferential resection margin (cCRM); American Joint Committee on Cancer (AJCC); neoadjuvant chemotherapy (NAC); central pelvis area (CPA); pelvic plexus and internal iliac area (PIA); obturator area (OA); statistical package for social science (SPSS);